FENOMENA PERCERAIAN DI KALANGAN WANITA KARIR TAHUN 2020-2021 PERSPEKTIF HUKUM ISLAM - Hijriah Mahrani Anwar; Lomba Sultan; Hadi Daeng Mapuna (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
The main problems in this study are: First: the rate of divorce among career women at the Sungguminasa Religious Court, Second: The impact of divorce among career women at the Sungguminasa Religious Court, and Third: The provisions of Islamic law on divorce among career women. The type of research used in this study is Case and Field Research. The results of this study indicate that the divorce rate for career women at the Sunggminasa Religious Court has increased every year but with a non-significant increase. The highest increase rate will occur in 2021 and the dominant career women who sue are from civil servants. The impact felt by divorced career women consists of positive and negative impacts. The perceived positive impact is more dominant than the negative. The positive impact experienced by career women is being free from heartache due to husbands who commit violence, do not provide a living, and have a third person from the relationship. Career women will also not feel difficulties in life because they already have a job and are more able to improve their career. The negative impact found from career women is the difficulty in economic terms to support children. Career women who want to divorce their husbands can file a lawsuit to the Religious Courts if the wife can no longer accept the behavior of her husband and wife in a condition that is not able to endure anymore with her husband, then both of them can agree to end their relationship. Keywords: Level, Impact, Career Woman Divorce